Biomimetic Medical Materials From Nanotechnology to 3D Bioprinting (Advances in Experimental Medicine and Biology,, 2018)
This volume outlines the current status in the field of biomimetic medical materials and illustrates research into their applications in tissue engineering. The book is divided into six parts, focusing on nano biomaterials, stem cells, tissue engineering, 3D printing, immune responses and intellectual property. Each chapter has its own introduction and outlines current research trends in a variety of applications of biomimetic medical materials. The biomimetic medical materials that are covered include functional hydrogels, nanoparticles for drug delivery and medicine, the 3D bioprinting of biomaterials, sensor materials, stem cell interactions with biomaterials, immune responses to biomaterials, biodegradable hard scaffolds for tissue engineering, as well as other important topics, like intellectual property. Each chapter is written by a team of experts. This volume attempts to introduce the biomimetic properties of biomedical materials within the context of our current understanding of the nanotechnology of nanoparticles and fibres and the macroscopic aspects of 3D bioprinting.